Between the desert and the sea: the prehistoric landscape of north-western Qatar - Spencer, Peter; Cuttler, Richard T.H.; al-Naimi, Faisal Abdulla; Davies, Talfan (Proceedings of the Seminar for Arabian Studies, 2015)
This paper details an evaluation of potential prehistoric sites within north-western Qatar identified through several successive seasons of remote sensing, extensive field survey, and excavation by the University of Birmingham. Through the application of modern survey methodologies based on global positioning system (GPS) and geographic information system (GIS) technology we explore the relationship between geospatial location and proximal geological, sedimentary, and environmental factors. In total we have to date identified approximately 7000 areas of potential archaeological interest in Qatar. These range chronologically from the prehistoric period to the late twentieth century. Site types vary from individual find spots, isolated cairns, artefact scatters, and structures to extensive sub-surface archaeological deposits, temporary camps, and permanent settlements. Of the 7000 areas, 2126 fall within the study area discussed in this paper, an area lying within the al-Shamāl, al-Khor, and al-Thakhira (al-Dhakhīrah) municipalities. The paper shall primarily focus upon the area of Wadi Debayan and Waab al-Debayan, detailing the results of excavations there before extending outwards to explore the relationships between areas of archaeological interest and their immediate environs.